2006
DOI: 10.1002/lt.20760
|View full text |Cite
|
Sign up to set email alerts
|

Successful ABO-incompatible pediatric liver transplantation utilizing standard immunosuppression with selective postoperative plasmapheresis

Abstract: Transplanting blood group A, B, or O (ABO)-incompatible (ABO-I) liver grafts has resulted in lower patient and graft survival with an increased incidence of vascular and biliary complications and rejection. We report that, without modification of our standard immunosuppression protocol, crossing blood groups is an acceptable option for children requiring liver transplantation. In our study, ABO-I liver grafts-regardless of recipient age-have comparable long-term survival (mean follow-up of 3.25 yr) with ABO-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 20 publications
1
54
0
1
Order By: Relevance
“…Earlier studies had reported increased risk of humoral and cellular rejection, arterial thrombosis and biliary complications after ABO incompatible liver transplants (ABOiLT) [53] . Measures such as peri-operative plasmapheresis [54] , and rituximab [55] have been used to lower peri-operative recipient antibody levels and thereby decrease the risk of these complications. ABOiLT in the pediatric population has been used more frequently and outcomes similar to ABO compatible LT have been achieved [56] .…”
Section: Abo Incompatible Liver Transplantsmentioning
confidence: 99%
“…Earlier studies had reported increased risk of humoral and cellular rejection, arterial thrombosis and biliary complications after ABO incompatible liver transplants (ABOiLT) [53] . Measures such as peri-operative plasmapheresis [54] , and rituximab [55] have been used to lower peri-operative recipient antibody levels and thereby decrease the risk of these complications. ABOiLT in the pediatric population has been used more frequently and outcomes similar to ABO compatible LT have been achieved [56] .…”
Section: Abo Incompatible Liver Transplantsmentioning
confidence: 99%
“…In a Swedish study of 10 adult blood group O recipients who received A 2 cadaveric grafts, patient and graft survival was 10/10 and 8/10 respectively at 8.5 mo median follow up with tacrolimus based protocol and initial immunosuppression with antithymocyte globulin, interleukin-2-receptor antagonists or anti-CD20 antibody [47] . In 16 pediatric ABOincompatible pediatric liver transplantation, Heffron et al reported one-year actuarial graft survival of 92% utilizing standard immunosuppression with selective postoperative plasmapheresis and without splenectomy [48] . Plasmapheresis may be useful by reducing the recipients' antibody titers before and after transplantation.…”
Section: Abo Incompatible Liver Transplantationmentioning
confidence: 99%
“…Particularly in recent years, advanced new immunosuppressive agents are developed, patient and graft survival rate after ILT has increased dramatically. However, high risk of complication after ILT, such as biliary complication[7], acute rejection[6], [8], [9] and hepatic artery thrombosis, is still a vital issue related to ILT.…”
Section: Introductionmentioning
confidence: 99%